Pendistribusian Zakat Bentuk Pinjaman Dalam Mengatasi Pedagang Usaha Mikro Dari Pinjaman Ribawi Di BAZNAS Kabupaten Merangin - Dori HP Putra; Agustiari Agustiari; Alan Rakhmat Putra (Gapenas Publisher, 2026)
This research is motivated by the phenomenon of the proliferation of micro business traders who make usury loans in conventional-based financial institutions. BAZNAS Merangin Regency is here to answer this phenomenon, by launching a program to distribute zakat funds in the form of loans for capital assistance for micro business traders. Therefore, this study aims to look at the distribution of zakat in the form of loans in overcoming micro merchants from usury loans, as well as to see what are the supporting factors and obstacles to the distribution of zakat on loans. The study used a descriptive qualitative approach. The research data uses primary data sources by using the Miles and Huberman model as a data analysis tool. This study shows that the distribution of zakat in the form of loans provided by BAZNAS has not been able to overcome all micro traders from usury loans. In terms of supporting factors for the distribution of zakat on loans is a revolving fund which has reached Rp. 1,820,000,000 and BAZNAS employees who are professional in the field of merchant development, and the inhibiting factor is the imbalance between the available funds and the amount of capital needed by traders, so that there are still many traders who choose to use usury loans as additional funds for business capital